2022
DOI: 10.1136/bmjopen-2022-065934
|View full text |Cite
|
Sign up to set email alerts
|

Early antibiotic use and incidence of necrotising enterocolitis in very preterm infants: a protocol for a UK based observational study using routinely recorded data

Abstract: IntroductionNecrotising enterocolitis (NEC) remains a major contributor to preterm mortality and morbidity. Prolonged duration of antibiotic therapy after delivery is associated with later NEC development but recent evidence suggests that absence of antibiotic treatment after delivery may also increase NEC risk. We will explore this controversy using a large pre-existing dataset of preterm infants in the UK.Methods and analysisThis is a retrospective cohort study using data from UK National Neonatal Research D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…In addition to antibiotic-induced changes on the gut microbiome, additional research into the direct effects of antibiotics on intestinal immunity is also needed. Ultimately, the inherent limitations of existing human studies warrant large prospective RCTs ( 105 ) as well as well-designed prospective observational studies ( 106 ) to study the impact of withholding early antibiotic use or limiting duration of exposure on NEC as well as other outcomes including late-onset sepsis and bronchopulmonary dysplasia. The NICU Antibiotics and Outcomes Trial (NANO) as well as other studies are beginning to address this question ( 106 108 ).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to antibiotic-induced changes on the gut microbiome, additional research into the direct effects of antibiotics on intestinal immunity is also needed. Ultimately, the inherent limitations of existing human studies warrant large prospective RCTs ( 105 ) as well as well-designed prospective observational studies ( 106 ) to study the impact of withholding early antibiotic use or limiting duration of exposure on NEC as well as other outcomes including late-onset sepsis and bronchopulmonary dysplasia. The NICU Antibiotics and Outcomes Trial (NANO) as well as other studies are beginning to address this question ( 106 108 ).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Ultimately, the inherent limitations of existing human studies warrant large prospective RCTs ( 105 ) as well as well-designed prospective observational studies ( 106 ) to study the impact of withholding early antibiotic use or limiting duration of exposure on NEC as well as other outcomes including late-onset sepsis and bronchopulmonary dysplasia. The NICU Antibiotics and Outcomes Trial (NANO) as well as other studies are beginning to address this question ( 106 108 ). Future clinical practice on early antibiotics use will likely be impacted by these ongoing studies.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Terapias con antibióticos postnatales: Los antibióticos empíricos se usan en los bebés prematuros inmediatamente después del nacimiento debido a la posibilidad de que una infección haya ocasionado el parto prematuro y por el alto riesgo de sepsis en bebés con muy bajo peso al nacer (Jin et al, 2019). Una corta duración de un tratamiento con antibióticos intravenosos después del nacimiento puede retardar la colonización, permitiendo al sistema inmunológico intestinal un periodo corto de adaptación lo que reduce el riesgo de ECN, en contraste un tratamiento prolongado causa disbiosis intestinal persistente lo que aumenta el riesgo de ECN (Jin et al, 2019) (Shen et al, 2022). En un estudio se menciona que del total de 11222 neonatos prematuros, el 89,1% tuvo exposición a antibióticos empíricos (EAE) por sospecha de sepsis de inicio tardío, de los cuales el 63,7% tuvieron EAE ≤ a 72h y el 25,4% a EAE prolongados >72h.…”
Section: Factores De Riesgo Neonatales Tempranos Y Postnatalesunclassified
“…Premature infants with low birth weight were more susceptible to infections, and there was evidence of an increased risk of ROP in these cases. Several studies have demonstrated an association between the incidence of early-onset sepsis in premature infants and an elevated risk as well as severity of ROP (Huang et al, 2019;Bonafiglia et al, 2022;Shen et al, 2022). This indicates that infections and inflammatory responses may have a vital role in the pathogenesis of ROP.…”
Section: Introductionmentioning
confidence: 99%